1996
DOI: 10.1080/01431169608948713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of forest fire risk by the analysis of environmental data and TM images

Abstract: The evaluation offorest fire risk is an important issue in Mediterranean areas where the long arid season often creates favourable conditions for the occurrence of fires. In this Letter three indices related to this risk have been produced and compared for the western part of the Elba Island (Central Italy). The first index is based on the analysis of environmental information layers (topography, vegetation and soil type) within a Land Information System, while the other two are derived from a summer Landsat T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…These results agree with those of several studies carried out in the European Mediterranean region (Leone et al 2003;Maselli et al 1996; de la Riva and Perez-Cabello 2005; de la Riva et al 2006) where the edges of rural-wildland interfaces were shown to be among the most susceptible areas to wildfires. In fact, fire susceptibility in this region is greatly affected by the level of landscape fragmentation and the so-called edge effect (Leone et al 2003).…”
Section: Catry Et Al 2007) Analyses Of Spatial Distributions Carriesupporting
confidence: 83%
“…These results agree with those of several studies carried out in the European Mediterranean region (Leone et al 2003;Maselli et al 1996; de la Riva and Perez-Cabello 2005; de la Riva et al 2006) where the edges of rural-wildland interfaces were shown to be among the most susceptible areas to wildfires. In fact, fire susceptibility in this region is greatly affected by the level of landscape fragmentation and the so-called edge effect (Leone et al 2003).…”
Section: Catry Et Al 2007) Analyses Of Spatial Distributions Carriesupporting
confidence: 83%
“…With accurate digital fuel maps, spatially explicit fire models such as Fire Area Simulator (FARSITE), FlamMap, and FS Pro (Finney, 1998;McDaniel, 2007) can simulate fires in order to evaluate and plan mitigation and suppression efforts or to support wildland fire use management strategies (Gouma and Chronopoulou-Sereli, 1998;Keane et al, 2001). Yet many natural resource agencies do not have adequate fuel maps, nor have they commonly collected fuel information during field inventories (Chuvieco and Congalton, 1989;Maselli et al, 1996;Keane et al, 2001;Reeves et al, 2006;McDaniel, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Integrating remotely sensed data into geographical information systems, with other information ( e.g. , Jain et al 1996, Maselli et al 1996), has also been used to ascertain the important factors, such as settlement and topography, favoring fires in particular forest landscapes. As more is known about fire behavior, the ultimate aim has focused on simulating as realistically as possible the actual behavior of fire.…”
mentioning
confidence: 99%